Thermal fatigue analysis and structural optimization of sliding composite leaf spring - Wang, Lubin; Chen, Wenliang; Lu, Xiaoqin (Frontiers in Materials, 2024)
The thermal failure mechanism of sliding composite leaf springs(SCLSs) is examined in this research. Bench fatigue testing is used in the experimental investigation of the thermal failure temperature and mode. The findings demonstrate that after 20 minutes, when the temperature reaches the glass transition temperature, cracks start to form around the bolt hole of the composite body.The findings from bench experiments indicate that thermal fatigue failure of SCLS can be divided into three main forms: delamination failure of the resin-rich layer, the resin-fiber interface, and fibre pull-out failure. The utilization of finite element simulation has demonstrated that when subjected to thermal load, the leaf spring's internal defects can lead to localized stress concentration. The structure of the spring end is optimized using the insulating panel scheme and the metal joint scheme. The thermal fatigue issue with SCLS is best addressed by the heat dissipation approach, according to bench tests.